The The Views of Music Education Students from the Bachelor’s Degree in Primary Education on the Impact that COVID-19 had on the Musical Tale as a Training Activity - Syroyid Syroyid, Bohdan; De Moya Martínez, María del Valle (Rastros Rostros, 2021)
Introduction. In Spain, due to COVID-19, a state of alarm was declared forcing a change from face-to-face teaching to an online model. This article reflects on this sudden transition and its impact on the didactic resource of the musical tale, understood as a story or a play with musical elements, an interdisciplinary approach aimed at acquiring key competences. Methodology. In the third year of the bachelor’s degree in Primary Education, students conducted an online group project based on a musical tale, which in previous editions was performed face-to-face. A sample of 86 participants from a population of 116 students of the Faculty of Education in Albacete (uclm) was surveyed to examine students’ views on this digital transition. Results. The efforts that Musical Education faculty made for smoothly transitioning to an online methodology was positively valued, although a preference in favor of face-to-face teaching over online teaching was reported. Benefits and drawbacks were identified in the staging of a musical fable in an online format, and other aspects that highlighted its didactic value. 90.1 % of the surveyed students expressed feeling adequately prepared to take this activity to a school class. Conclusions. The musical fable as a didactic resource was positively valued by students, and its implementation to the online format was satisfactory.